Leukocytes in Cerebral Thrombus Respond to Large-Vessel Occlusion in a Time-Dependent Manner and the Association of NETs With Collateral Flow - Chen, Xi; Wang, Li; Jiang, Meiling; Lin, Lin; Ba, Zhaojing; Tian, Hao; Li, Guangjian; Chen, Lin; Liu, Qu; Hou, Xianhua; Wu, Min; Liu, Lu; et al. (Frontiers in Immunology, 2022)
Thrombus components are dynamically influenced by local blood flow and blood immune cells. After large vessel occlusion stroke, changes in cerebral thrombus are unclear. Here we assessed a total of 206 cerebral thrombi from patients with ischemic stroke undergoing endovascular thrombectomy. Thrombi were categorized by time to reperfusion of < 4 h (T4), 4–8 h (T4–8) and > 8 h (T8). The cellular compositions in thrombus were analyzed and relevant clinical features were compared. Both white blood cells and neutrophils were increased and then decreased in thrombus with time to reperfusion, which were positively correlated with those in peripheral blood. Neutrophil extracellular traps (NET) content in thrombus were correlated with the degree of neurological impairment of patients. Moreover, with prolonged time to reperfusion, patients showed a trend of better collateral grade, which was associated with a lower NET content in the thrombus. In conclusion, the present results reveal the relationship between time-related endovascular immune response and clinical symptoms post stroke from the perspective of thrombus and peripheral blood. Time-related pathological changes of cerebral thrombus may not be the direct cause for the difficulty in thrombolysis and thrombectomy. A low NET content in thrombi indicates excellent collateral flow, which suggests that treatments targeting NETs in thrombi might be beneficial for early neurological protection.